2014
DOI: 10.3892/etm.2014.2123
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations on 8p21-p23 are the most frequent genetic events in stage I squamous cell carcinoma of the lung

Abstract: Genetic alterations in the early stages of cancer have a close correlation with tumor initiation and potentially activate downstream pathways implicated in tumor progression; however, the method of initiation in sporadic neoplasias is largely unknown. In this study, whole-genome microarray-comparative genomic hybridization was performed to identify the early genetic alterations that define the prognosis of patients with stage I squamous cell carcinoma (SCC) of the lung. The most striking finding was the high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Higher frequency of 8p23.1 loss was found to be significant in the CHOICE study. Genes in this region, such as MSRA , MFHAS1 , DEFB106A , and DEFB105A , play an important role in the initiation and progression of lung SQCC 22 . Focal alteration at 14q11.2 containing olfactory receptor family genes was specifically identified in lung ADC.…”
Section: Discussionmentioning
confidence: 99%
“…Higher frequency of 8p23.1 loss was found to be significant in the CHOICE study. Genes in this region, such as MSRA , MFHAS1 , DEFB106A , and DEFB105A , play an important role in the initiation and progression of lung SQCC 22 . Focal alteration at 14q11.2 containing olfactory receptor family genes was specifically identified in lung ADC.…”
Section: Discussionmentioning
confidence: 99%
“…Loss at 1p, mainly deletion of FAM46C and CDKN2C, has been shown to be associated with adverse prognosis in MM (26)(27)(28) and also with progression of SMM to MM (29). It has been shown that 8p loss plays an important role in the pathogenesis of various tumor disorders (30)(31)(32). However, impact on survival of MM patients was not found in a previous study (33).…”
Section: Discussionmentioning
confidence: 97%
“…Rs1600249, located at chromosome region 8p23.1, is 394KB away from AF131215.2 . Genetic alterations in the distal part of 8p21.1‐p23.3 frequently occur in the early stage of lung cancer . Meanwhile, the size of these alterations, as well as their frequency, tends to increase during lung cancer progression .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alterations in the distal part of 8p21.1-p23.3 frequently occur in the early stage of lung cancer. 59 Meanwhile, the size of these alterations, as well as their frequency, tends to increase during lung cancer progression. 60,61 Coexpressed genes with AF131215.2 were mainly enriched in the thyroid hormone signaling pathway.…”
Section: Discussionmentioning
confidence: 99%